THE UNINTENDED CONSEQUENCES OF REDUCED SKILLED NURSING FACILITY LENGTH OF STAY. (11th November 2018) - Mor, V; McHugh, J P; Shield, R R; Winblad, U; Gadbois, E A; Tyler, D A
Abstract: We conducted interviews with 70 staff in 25 SNFs to identify key challenges from reduced lengths of stay (LOS) in SNFs. We used risk adjusted SNF median LOS to identify the SNFs with reductions in LOS (N=12) and with no reductions in LOS (N=13). Regardless of reductions in LOS, challenges that were reported included frequent and more complicated re-authorization processes, patients becoming responsible for costs, and patient discharges to home that staff felt were unsafe. With reduced LOS, SNF leaders reported pressures to discharge patients within prescribed time limits. Some SNF leaders reported they instituted programs and processes for following up with patients after discharge that helped alleviate concerns about patients, but resulted in non-reimbursable costs for the SNFs. Shorter SNF LOS has resulted in unexpected and undesired challenges and costs for SNFs and possible unintended consequences for PAC patients that warrant further scrutiny and reappraisal.